18β‐glycyrrhetinic acid improves high‐intensity exercise performance by promoting glucose‐dependent energy production and inhibiting oxidative stress in mice. (28th October 2021) - Ma, Xuan; Chen, Hui; Cao, Lixing; Zhao, Shuang; Zhao, Chong; Yin, Shutao; Hu, Hongbo
Abstract : It has been shown that 18β‐glycyrrhetinic acid (18β‐GA), the main bioactive compound of licorice, can modulate oxidative stress and metabolic processes in liver and skin. Given the critical role of oxidative stress and energy metabolism in exercise‐induced fatigue, we hypothesized that 18β‐GA could exert an ergogenic action by inhibiting excess reactive oxygen species (ROS) induction and promoting energy production in muscles. Mice were gavage‐fed with 18β‐GA for four consecutive days. Running ability was assessed based on the exhaustive treadmill test with high‐ and moderate‐intensity. Western blot analysis, enzyme‐linked immunosorbent assay, and immunofluorescence staining were used to measure the changes of muscle fatigue‐related markers, oxidative stress status, and energy metabolism in response to 18β‐GA exposure. Treatment with 18β‐GA significantly increased the exhaustive running distance ( 37%) in the high‐intensity exercise, but not in the moderate‐intensity exercise. Mechanistically, reduction of oxidative stress and induction of antioxidants (SOD, CAT, and GSH) by 18β‐GA were observed. Moreover, 18β‐GA treatment caused an improved preservation of muscle glycogen (12%), which was associated with upregulation of glucose transporter 4 (GLUT4) (91%) and increased insulin level (17%). The findings of the present study clearly suggest that 18β‐GA holds excellent potential as a novel bioactive agent against high‐intensity exercise‐induced fatigue.